Insights From the Genome Sequence of Mycobacterium paragordonae, a Potential Novel Live Vaccine for Preventing Mycobacterial Infections: The Putative Role of Type VII Secretion Systems for an Intracellular Lifestyle Within Free-Living Environmental Predators - Kim, Byoung-Jun; Cha, Ga-Yeong; Kim, Bo-Ram; Kook, Yoon-Hoh; Kim, Bum-Joon (Frontiers in Microbiology, 2019)
Mycobacterium paragordonae (Mpg) is a temperature-sensitive Mycobacterium species that can grow at permissive temperatures but fails to grow above 37 °C. Due to this unique growth trait, Mpg has recently been proposed as a novel live vaccine candidate for the prevention of mycobacterial infections. Furthermore, the increasing frequency of the isolation of Mpg from water supply systems led us to hypothesize that the free-living amoeba system is the natural reservoir of Mpg. In this study, we report the complete 6.7-Mb genome sequence of Mpg and show that this genome comprises four different plasmids with lengths of 305 kb (pMpg-1), 144 kb (pMpg-2), 26 kb (pMpg-3) and 17 kb (pMpg-4). The first two plasmids, pMpg-1 and -2, encode distinct Type VII secretion systems (T7SS), ESX-P5 and ESX-2, respectively. Genome-based phylogeny indicated that Mpg is the closest relative to M. gordonae, which has a 7.7-Mb genome; phylogenetic analysis revealed an average of 86.68% nucleotide identity between these two species. The most important feature of Mpg genome is the acquisition of massive genes related to T7SS, which may have had effect on adaptation to their intracellular lifestyle within free-living environmental predators, such as amoeba. Comparisons of the resistance to bacterial killing within amoeba indicated that Mpg exhibited stronger resistance to amoeba killing compared to M. gordonae and M. marinum, further supporting our genome-based findings indicating the special adaptation of Mpg to free-living amoeba. We also determined that, among the strains studied, there were more shared CDS between M. tuberculosis and Mpg. In addition, the presence of diverse T7SSs in the Mpg genome, including an intact ESX-1, may suggest the feasibility of Mpg as a novel tuberculosis vaccine. Our data highlight a significant role of lateral gene transfer in the evolution of mycobacteria for niche diversification and for increasing the intracellular survival capacity.